2012
DOI: 10.2135/cropsci2011.11.0581
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Optimum Plant Temperature of Cotton Physiology and Yield to Improve Plant‐Based Irrigation Scheduling

Abstract: A plant-based thermal optinnum approach to irrigation scheduling provides potential benefits in that water applications are scheduled on the basis of plant response to vi/ater status. Such irrigation systems require a defined thermal optimum for the crop and while such optimum values have been identified for cotton {Gossyplum hirsutum L.) cultivars in the United States, tinere is no information of this type for cultivars common in Australian production. This paper outlines a threefold approach to determining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 34 publications
4
35
0
Order By: Relevance
“…Cotton sowing is also one of the most important critical aspects which leads to phenological development; conversion of assimilates and biomass to economic yield (Ali et al, 2009). Early sowing (February and March) experiences cold temperature (<12 °C) stress which causes stand loss and delays in all developmental and phenological stages (Constable and Bange, 2006); poor biomass accumulation and ultimately lower seed cotton yield (Pettigrew 2008;Conaty et al, 2012). Early post emergent plants exposed to cooler nights (<12 °C) called cold shock have to face cold stress and it slows down the developmental rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cotton sowing is also one of the most important critical aspects which leads to phenological development; conversion of assimilates and biomass to economic yield (Ali et al, 2009). Early sowing (February and March) experiences cold temperature (<12 °C) stress which causes stand loss and delays in all developmental and phenological stages (Constable and Bange, 2006); poor biomass accumulation and ultimately lower seed cotton yield (Pettigrew 2008;Conaty et al, 2012). Early post emergent plants exposed to cooler nights (<12 °C) called cold shock have to face cold stress and it slows down the developmental rates.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton-wheat cropping system is located in high temperature zone where summer day temperature exceeds 45 °C (heat stress >35 °C) which may adversely affect cotton growth and development and ultimately seed cotton yield (Rahman et al, 2004). Physiological and metabolic processes of cotton have thermal range from 23-32 °C which is considered as optimal for growth and development (Pettigrew and Johnson, 2005;Conaty et al, 2012). Late planting is usually resulted in yield reduction due to short reproductive phase as compared to early planting.…”
Section: Introductionmentioning
confidence: 99%
“…Pettigrew (2008) observed that when temperature exceeds 1°C from ambient air temperature (35 to 38°C) during three years of study, the warm regime reduced lint yield by 10% supporting the work of Burke et al (1988) that 32°C is the optimum temperature for cotton crop. Conaty et al (2012) found cotton yield reduction when temperature was increased above 30°C. Cottee et al (2008) examined yield reduction under heat stress regime (artificially created) over the ambient temperature of field conditions where temperature remained above 35°C throughout cotton growing season.…”
Section: Relationship Between Nffb and Ph; Ph And Number Of Monopodiamentioning
confidence: 96%
“…Recent studies conducted on corn and cotton [55][56][57] raise research questions about the relationships between canopy temperature, hay yield and quality, and WP, which could be addressed through specific applied research efforts, and can lead to development of plant-based irrigation scheduling for resource-efficient alfalfa production with SDI.…”
Section: Plant-based Irrigation Managementmentioning
confidence: 99%